Common Fixed Point Theorems for Probabilistic Nearly Densifying Mappings - Aeshah Hassan Zakri; Sumitra Dalal; Sunny Chauhan; Jelena Vujaković (Abstract and Applied Analysis)
The aim of this paper is to prove some coincidence and common fixed point theorems for probabilistic nearly densifying mappings in complete Menger spaces. Our results improve the results of Chamola et al. (1991), Dimri and Pant (2002), and Pant et al. (2004) and extend the results of Khan and Liu (1997) in the framework of probabilistic settings.